Towards the Development of Bilingualism in the Colombian Context - Rojas Barreto, Lisseth (Universidad Pedagógica y Tecnológica de Colombia, 2011)
AbstractThe promotion of bilingualism since the beginning of schooling has become one of the major goals of the Educational Policies in Colombia. Therefore the differenteducative Institutions around the country should go hand in hand towards that goal, through the training of their administrative and teaching staff. That training should involve all implications that the implementation of bilingualism in the different levels of Basic Education entails. This article tackles some issues which canlight and contribute to such implementation in the Colombian context. Key Words: Bilingualism, Early and Late Bilingualism, Play-Based Activities, Interactional Spaces, Multilingualism. ResumenLa promoción y desarrollo del bilingüismo desde los primeros grados de básica primaria se ha convertido en una de las mayores metas de las políticas educacionales en Colombia. Por esta razón, las diferentes Instituciones educativas a lo largo del país deben ir a la par con dicho fin a través da la capacitación de su personal administrativoy de enseñanza en este tema. Dicho entrenamiento debe involucrar todas lasimplicaciones que abarca la implementación del bilingüismo en los diferentes niveles de básica primaria.  Este artículo aborda algunos aspectos que pueden contribuir  a dicha implementación en el contexto colombiano. Palabras clave: Bilingüismo, Bilingüismo temprano y tardío, Actividades basadas en el juego, Espacios interactivos,Multilingüismo.